Incidence, Trends and In-Hospital Course and Outcomes of Torsades de Pointes - Shehadeh, Malik; Sudesh, Saurabh; Pollevick, Matias; Rubin, Geoffrey A.; Wan, Elaine Y.; Saluja, Deepak; Dizon, Jose M.; Biviano, Angelo; Garan, Hasan; Yarmohammadi, Hirad (Cardiology and Cardiovascular Medicine, 2024)
Background: Torsades de Pointes (TdP) is a polymorphic ventricular tachycardia (VT) that occurs in the setting of QT prolongation. While it can terminate spontaneously, TdP can also degenerate into ventricular fibrillation and results in sudden cardiac death. Objective: To investigate the incidence, trends, and in-hospital outcomes of TdP events. Methods: Our hospital database was queried from January 1, 2016- December 31, 2020 to identify patients with polymorphic VT. The mode of onset, telemetry strips and ECGs were reviewed to confirm the diagnosis of TdP. The in-hospital course, outcomes and predictors of in-hospital mortality were evaluated. Results: Of 3,575 patients with VT episodes, 74 patients had confirmed TdP events (56.8% males, mean age 60.3 ± 17.1 years). The number of TdP cases remained stable throughout 2016-2020, ranging from 12-16 per year. The proportion of TdP/VT cases was significantly higher in 2020 during COVID-19 pandemic compared to prior years (6.8% vs 1.7%, p<.001), due mainly to a four-fold decrease in overall VT cases presented to the hospital that year. Forty-two patients (56.8%) needed defibrillation while the rest were hemodynamically stable. Fifteen patients (20.3%) died during admission. The proportion of TdP patients who died during admission was not significantly different across 2016-2020 (P=.76). Conclusion: There was a relative and significant increase in the number of TdP as a proportion of VT cases in 2020 during COVID-19 pandemic year when it was compared to the previous years. However, in-hospital all-cause mortality rate was not significantly different during the 5-year study period.